Pemanfaatan Moringa oleifera melalui Proses Elektroflotasi Biokoagulasi dalam Penjernihan Limbah Cair Laboratorium - Setyowati, Rr Diah Nugraheni; Wijayanti, Arik; Suriani, Efa; Adila, Surya Puspa; Al Hikmi, Achmad Syahri (Fakultas Teknik Universitas Khairun, 2024)
The problem of waste was a serious concern of the world, as well as for the government and the people of Indonesia. The particular concern regarding waste does not only apply in the industrial and trade sectors, but also in other sectors that generate waste such as in the tourwasm, health, research development, and education sectors, especially those that have integration laboratory. The biocoagulant used were moringa seeds with a dose variation of 0.025; 0.05; and 0.1 grams/250 mL. The electroflotation process was carried out electrodes, namely graphite electrodes at the anode and stainless steel at the cathode with a constant voltage of DC 21 V for 60 minutes. The effectiveness of the electroflotation-biocoagulation process was valuated by looking at the decrease in the electrical conductivity (EC), total dwassolved solids (TDS), turbidity, metal Pb and Cu. The study's result was the electroflotation-biocoagulation process was more effective than the electroflotation and coagulation processes. Electrical conductivity (EC) was successfully reduced to 9.76% by 0.1 gram/500 mL, TDS (dwassolved solids) was reduced to 8.78% by moringa oleifera, waste turbidity was decreased to 91.70%, the concentration of Pb was reduced to 12.80 % and Cu was reduced to 0,119.Â